An Analysis of English Mispronunciations by EFL Students - I Made Yogi Marantika; Ni Putu Cahyani Putri Utami; Fina Avianti Harianja (RETORIKA: Jurnal Ilmu Bahasa, 2024)
English has distinctive characteristics that may differ from those of a student’s native language, and it is essential to grasp the differences. That is why it is crucial for students studying English as a Foreign Language (EFL) to understand the nuances of English pronunciation because a mispronunciation of a word may result in a lack of comprehension. The objective of this study is to identify the mispronunciation made by students in their pursuit of fluency in English. It employed a descriptive qualitative approach. In order to collect the data, the EFL students were required to read ten prepared English sentences, which had been selected according to the topic that they had been learning. In this study, Davies' theory was used as a reference, particularly in relation to English phonemes. The results demonstrated that there were pronunciation errors in six vowel sounds, three diphthongs, and six consonant sounds. When pronouncing a word in a sentence, EFL students tend to be influenced by their first language. Therefore, the acquisition of knowledge regarding the phonemic differences inherent to the English language will have a beneficial effect on the advancement of the language skills of students engaged in English as a Foreign Language (EFL) studies.